Reduction of Li+ within a borate anion - Li, Haokun; Yao, Jiachen; Xu, Gan; Yiu, Shek-Man; Siu, Chi-Kit; Wang, Zhen; Peng, Yung-Kang; Xie, Yi; Wang, Ying; Lu, Zhenpin (Nature communications, 2024)
Group 1 elements exhibit the lowest electronegativity values in the Periodic Table. The chemical reduction of Group 1 metal cations M + to M(0) is extremely challenging. Common tetraaryl borates demonstrate limited redox properties and are prone to decomposition upon oxidation. In this study, by employing simple yet versatile bipyridines as ligands, we synthesized a series of redox-active borate anions characterized by NMR and X-ray single-crystal diffraction. Notably, the borate anion can realize the reduction of Li + , generating elemental lithium metal and boron radical, thereby demonstrating its potent reducing ability. Furthermore, it can serve as a powerful two-electron-reducing reagent and be readily applied in various reductive homo-coupling reactions and Birch reduction of acridine. Additionally, this borate anion demonstrates its catalytic ability in the selective two-electron reduction of CO 2 into CO. Chemical reduction of alkali cations to their metals is extremely challenging. Here, the authors synthesized a series of redox-active borate anions stabilized by bipyridine ligands which can reduce lithium ions generating elemental lithium metal and borate radicals.